2003
DOI: 10.1007/s00127-003-0594-7
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia: illness impact on family members in a traditional society - rural Ethiopia

Abstract: Negative impact of schizophrenia on family members is substantial even in traditional societies such as those in Ethiopia where family network is strong and important. The scarce existing services in the developing countries should include family interventions and support at least in the form of educating the family members about the nature of schizophrenia illness and dealing with its stigma and family burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 17 publications
10
72
0
Order By: Relevance
“…This finding was similar to findings of an Ethiopian rural community-based study involving 301 patients with schizophrenia and their close relatives where financial difficulty was the most frequently endorsed problem (74.4% of the cases) among the family burden domains across both sexes. 7 However, gender differences were seen in financial and work burden domains with female relatives reporting being more affected than male relatives. Several other studies have also reported financial difficulties as mental illness had a negative effect on the income of the family.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This finding was similar to findings of an Ethiopian rural community-based study involving 301 patients with schizophrenia and their close relatives where financial difficulty was the most frequently endorsed problem (74.4% of the cases) among the family burden domains across both sexes. 7 However, gender differences were seen in financial and work burden domains with female relatives reporting being more affected than male relatives. Several other studies have also reported financial difficulties as mental illness had a negative effect on the income of the family.…”
Section: Discussionmentioning
confidence: 96%
“…This finding corroborates what was reported in other studies where disorganised symptoms rather than (primary features of) the actual diagnosis (as classified by the fourth edition of the Diagnostic and Statistical Manual for Mental Disorders [DSM-IV]) 12 , were the most important factors affecting family members in all family burden domains. 6,7,11 Abuse of alcohol by mentally ill patients may have led either to misuse of badly needed family resources or to unacceptable behaviour while under the influence of alcohol. Behaviours that were exhibited beyond the confines of the home, for example, wandering, may have posed a threat to the patient and others outside the family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suicide rates are high and psychiatry and mental illness are taboo concepts. Finally, the burden on families within the 'developing world', already struggling with basic survival needs, is great 46 -support for families and caregivers is generally non-existent.…”
Section: Non-who Data On Outcomementioning
confidence: 99%
“…In Ethiopia, Shibre et al (20) looked at the impact of schizophrenia on 300 family caregivers in traditional rural communities. Relatives experienced financial difficulties, constraints on their social life, reduced opportunities to work and strained family relationships.…”
Section: The Socio-economic Impact Of Poor Mental Healthmentioning
confidence: 99%